2007
DOI: 10.1128/jcm.00715-07
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Multiple-Locus Variable-Number Tandem Repeats in Salmonella enterica Serovar Typhimurium

Abstract: Variable-number tandem repeats (VNTRs) may evolve so rapidly that multiple profiles emerge during an outbreak. A total of 190 isolates from eight Salmonella enterica serovar Typhimurium outbreaks and 15 isolates from seven patients were analyzed by pulsed-field gel electrophoresis and VNTR typing. Small changes in loci were noted; otherwise, the VNTR profiles were stable during the course of the outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 14 publications
0
39
0
3
Order By: Relevance
“…Twenty isolates produced 1 of 3 related profi les (loci of VNTR profi les are ordered STTR9-STTR5-STTR6-STTR10pl-STTR3): 1-4-0-0-3, 9 isolates; 1-5-0-0-3, 3 isolates; or 1-6-0-0-3, 8 isolates. Alleles 4 and 5, and 5 and 6 at locus STTR5 only differed by an extra 6-bp repeat, which suggests a clonal relationship between the qnrS1-positive S. Typhimurium in this study (Table) (8). S. Typhimurium isolates with the 1-6-0-0-3 profi le have been isolated from tourists returning from Asia (7), which suggests that the UK qnrS1-positive S. Typhimurium isolates have originated in the Far East.…”
Section: Plasmid-mediated Quinolone Resistance In Salmonella Entericamentioning
confidence: 82%
“…Twenty isolates produced 1 of 3 related profi les (loci of VNTR profi les are ordered STTR9-STTR5-STTR6-STTR10pl-STTR3): 1-4-0-0-3, 9 isolates; 1-5-0-0-3, 3 isolates; or 1-6-0-0-3, 8 isolates. Alleles 4 and 5, and 5 and 6 at locus STTR5 only differed by an extra 6-bp repeat, which suggests a clonal relationship between the qnrS1-positive S. Typhimurium in this study (Table) (8). S. Typhimurium isolates with the 1-6-0-0-3 profi le have been isolated from tourists returning from Asia (7), which suggests that the UK qnrS1-positive S. Typhimurium isolates have originated in the Far East.…”
Section: Plasmid-mediated Quinolone Resistance In Salmonella Entericamentioning
confidence: 82%
“…To accommodate such VOL. 47, 2009 MLVA FOR TYPING OF GLOBAL SEROVAR TYPHI ISOLATES 2371 on May 9, 2018 by guest http://jcm.asm.org/ variation for epidemiological typing, it has been suggested that a single locus variant may be classified as belonging to the same outbreak (9,22). The stability of TR1 and TR2 used in this study was tested in laboratory culture using four isolates by Liu et al (20).…”
Section: Resultsmentioning
confidence: 99%
“…However, a quickly evolving marker may vary during an outbreak, and such a marker may be considered unstable. SAL16 (STTR5) which was also used in the serovar Typhimurium MLVA scheme has been shown to vary in three of the eight different serovar Typhimurium outbreaks studied (9). To accommodate such VOL.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the technique can be multiplexed and automated and is conducive to rapid and relatively high-throughput strain typing. MLVA assays are relatively robust (5,(15)(16)(17) and, while not perfect, they can provide phylogenetic information even with a limited number of loci (13,18). While access to a sequenced genome dramatically speeds the ability to establish new assays (3), it is not a requisite to assay development.…”
mentioning
confidence: 99%
“…It is one of the most reproducible and highly discriminatory typing techniques and has been widely and successfully used for a variety of Salmonella enterica serovars (12,15); for many situations, PFGE is capable of discriminating between closely related strains. In addition, the use of the assay to analyze different serovars does not require a great deal of modification, as might be required with procedures that are dependent on PCR.…”
mentioning
confidence: 99%